KEBIASAAN MAKAN IKAN BILIH (Mystacoleucus padangensis Bleeker) DI SUNGAI NABORSAHAN, KECAMATAN AJIBATA, KABUPATEN TOBA SAMOSIR, SUMATERA UTARA - Hafiz Muhammad; Yunasfi Djayus; Ani Suryanti (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2014)
The decline of fish populations bilih (Mystacoleucus padangensis Bleeker) caused by fishing activity and the availability of natural food in the River Naborsahan closely related to the physico-chemical factors of the river. The purpose of this study was to determine the feeding habits of fish bilih (Mystacoleucus padangensis Bleeker). This study was conducted in June - July with purposive random sampling method. The results showed that the natural food of bilih fish is phytoplankton from the genus Rhizosolenia, Synedra, Aulacoseira, Gonatozygon, Pinnularia, Closterium, Surirella, Gyrosigma, Melosira, Oscillatoria and zooplankton from genus Creseis, tubifex and Daphnia. Natural food that became the main food of bilih fish is phytoplankton from the genus Synedra with IP (Index Preporedence) > 40% fish is 98.9%. Natural feed becomes additional food of bilih fish <4% that is Rhizosolenia, Aulacoseira, Gonatozygon, Pinnularia, Closterium, Surirella, Gyrosigma, Melosira, Oscillatoria, Creseis, Tubifex and Daphnia. Measurement results of physico-chemical factors water good enough for the availability of natural food and life of bilih fish (Mystacoleucus padangensis Bleeker).Keywords: Fish bilih (Mystacoleucus padangensis Bleeker), Food Habits, Naborsahan River.